2016
DOI: 10.1002/ajmg.c.31525
|View full text |Cite
|
Sign up to set email alerts
|

Procedures in the 1st year of life for children with trisomy 13 and trisomy 18, a 25‐year, single‐center review

Abstract: Care of the child born with trisomy 13 or 18 has evolved over the past few decades, leading to increased healthcare utilization. We hypothesized that there has been an increase in procedures across all intensity types, including major, invasive procedures. We performed a retrospective-cohort study of children with trisomy 13 or 18 from 1990 to 2014 in a quaternary, free-standing children's hospital. Children were identified using ICD-9 billing diagnoses. Procedures were identified during these encounters and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Despite the poor prognosis for T13 and T18, there have been recent reports of long-term survival of more than 5 years age (Janvier, Farlow, & Barrington, 2016; Janvier, Farlow, & Wilfond, 2012; Meyer et al, 2016; Wu et al, 2013). Growing evidence has shown that medical and surgical interventions can prolong survival (Domingo, Carey, Eckhauser, Wilkes, & Menon, 2018; Josephsen, Armbrecht, Braddock, & Cibulskis, 2016; Kaneko et al, 2008; Kosho, Kuniba, Tanikawa, Hashimoto, & Sakurai, 2013; Nelson et al, 2016; Nelson, Hexem, & Feudtner, 2012; Tsukada, Imataka, Suzumura, & Arisaka, 2012). Regional variations in screening and care for infants with T13 or T18 and differences in public, parental, or professional perceptions pose ethical challenges for parents and professionals when encountering a prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the poor prognosis for T13 and T18, there have been recent reports of long-term survival of more than 5 years age (Janvier, Farlow, & Barrington, 2016; Janvier, Farlow, & Wilfond, 2012; Meyer et al, 2016; Wu et al, 2013). Growing evidence has shown that medical and surgical interventions can prolong survival (Domingo, Carey, Eckhauser, Wilkes, & Menon, 2018; Josephsen, Armbrecht, Braddock, & Cibulskis, 2016; Kaneko et al, 2008; Kosho, Kuniba, Tanikawa, Hashimoto, & Sakurai, 2013; Nelson et al, 2016; Nelson, Hexem, & Feudtner, 2012; Tsukada, Imataka, Suzumura, & Arisaka, 2012). Regional variations in screening and care for infants with T13 or T18 and differences in public, parental, or professional perceptions pose ethical challenges for parents and professionals when encountering a prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, survival to 1 year of age is poor, at approximately 10% (Goel et al, 2019). Previously defined as lethal conditions, medical, and surgical interventions offered in these populations are increasing (Josephsen, Armbrecht, Braddock, & Cibulskis, 2016; Nelson, Rosella, Mahant, & Guttmann, 2016; Shibuya et al, 2018) as patients are surviving into childhood (Meyer et al, 2016) and even adulthood (Patterson et al, 2017; Tunca, Kadandale, & Pivnick, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Three infants with cardiac malformations initially received comfort care during the birth hospitalization and went home with hospice (cases [12][13][14]. They all represented for admission, receiving a variety of interventions during their readmissions including cardiac catheterization, mechanical ventilation, and lumbar puncture.…”
Section: Resultsmentioning
confidence: 99%
“…Our study is similar to other studies that demonstrate a wide and growing range of interventions provided to children with T13 or T18, including cardiac surgical procedures, noncardiac surgical procedures (orthopaedic, ear/ nose/throat, and gastrointestinal procedures and tracheostomy placement) as well as less-aggressive medical interventions. 4,14,23,24 Other authors have concentrated on documenting the parents' perspective 20,25,26 ; however, there is less information published on how care provided to individual patients with T13 or T18 changes over time. Our study expands this literature by outlining patterns of care provided that are not firmly situated in comfort care or in intervention but along a continuum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation